Evaluation of the Harmony of Smile Appearance with Personality Traits in Patients Applying for Smile Makeover - Sajad Babaei; Mehrdad Kazemian; Fateme Aghaee; Arash Ghodousi (مجله دانشکده دندانپزشکی اصفهان, 2022)
Dentists have always sought to harmonize the shapes of the teeth with the entire face based on parameters such as gender, personality, and age. The Visagism concept helps dentists to be able to create a smile that is not only for esthetics but also in harmony with all the psychological characteristics of the patient. The aim of this study was to investigate the match between smile design and personality traits of patients applying for smile design.Materials & Methods:This is a descriptive-analytical study. Standard photographs in three different modes of rest, gentle smile, and full smile were taken from 104 patients aged 30-18 years referred to the School of Dentistry of the Islamic Azad University of Isfahan in 2016 for smile design. Patients were given a questionnaire about temperament and an interview questionnaire for understanding their dental needs. The photos were checked by one professional observer and classified according to the Visagism concept and the photos were analyzed with the results of the questionnaire and the interview form. The Data were analyzed by Chi-square and One-Way ANOVA test (p value < 0.05).Results:Consistency percentage between personality and smile was 71.1% (p value < 0.0001). The most consistent in these 2 factors was Phlegmatic temperament (81.1%).Conclusion:Since there is a significant relationship between smile design and personality, it is recommended that in reconstructing a smile dentists should not limit themselves to aesthetic aspects from a dental point of view, but by creating a patient's psychological evaluation, create an esthetic smile plan in harmony with patients' psychological characteristics.